Mappacci Film Marketing Communication Strategy in Penetrating the National Film Industry - Sunarti Sunarti; Yusmanizar Yusmanizar; Muhammad Yusuf Ar (Borong Newinera Publisher, 2026)
This study aims to examine and analyze the marketing communication strategies of the film Mappacci, as well as to identify the supporting and inhibiting factors in its distribution process toward entering the national film industry. The research was conducted at PT 786 Production and Timur Picture. Data were collected through observation, interviews, and documentation studies, then analyzed to provide a comprehensive picture of the film’s marketing strategy. The study discusses how the film Mappacci managed to penetrate the national film industry despite the challenges faced by local films in competing with dominant national and international productions. The findings reveal that Mappacci implemented an Integrated Marketing Communication (IMC) approach by combining both online and offline communication channels. However, not all elements of the marketing mix (7P) were optimally utilized. Supporting factors for its success include the strength of local cultural narratives and strong community engagement, while inhibiting factors involve limited distribution networks, restricted market access, and constrained promotional capacity. This study concludes that the success of Mappacci cannot be separated from the implementation of an integrated marketing communication strategy. Nevertheless, further optimization of all marketing mix elements is required to achieve more sustainable competitiveness in the national film industry.